(untitled) (Communications in Computational Chemistry, 2022)
The polymer with D-A structure has been certified a significant role as donor materials of organic solar cells (OSCs) for its outstanding light absorption. In this work, the properties of pyridine based and fused cyclic based D-A polymer was studied by means of DFT and TD-DFT theory under PBE0/6-31G(d) level. Based on the reported polymer D1, pyridine and fused cyclic were introduced to D2, D3 and D4. Compared with polymer lacking the pyridine and fused cyclic, the pyridine and fused cyclic based exhibits better planarity, lower HOMO energy and broader absorption properties, which are helpful to get a higher V_oc and J_sc. Moreover, fused cyclic based as well as pyridine monocycle and pyridine fused cyclic based polymer shows the ability to enhance the hole transfer rate. Hence, the approach of introducing pyridine and fused cyclics to polymer donor is a feasible way to modulate the electron-withdrawing capability in D-A polymer chain thereby promotes the performance of the OPV devices.